Pop kill - Johnson, Dave, 1966-; Palmiotti, Jimmy (Mad Cave Studios, 2025)
"Imagine a world where the two dominant and competing Cola companies, each worth billions, are owned by former conjoined twins who are now separated and have grown to hate each other so much they hire assassins, saboteurs, and espionage personnel to meddle with each other on a daily basis. This is the story about brotherly love run afoul, and the people they enlist to do their dirty work."--